Evolving 'places': The paradigmatic shift in the role of the fashion designer. Issue 4 (1st October 2021) - Faerm, Steven
This study examines the concept of 'place' in the design process and the evolving role of the fashion designer. The contemporary fashion marketplace has reached unprecedented levels of abundance. This is altering society's relationship with design. Consumers' basic needs are being over-met and have moved well beyond the material realm; consumers are increasingly driven by their search for meaning and emotional fulfilment through design. The result of this process is the altering of their perception of design 'value' from the tangible to the intangible. While the traditional values of aesthetics and function remain essential components to design, a product's ability to deliver 'emotional value' to the user must increasingly become the focus for designers. To succeed, a designer must shift his/her sense of 'place' ‐ namely, the figurative 'place' from which he/she designs. Rather than creating fashion from myopic, personal biases, future designers must enter the 'place' of the design process by rigorously researching their consumers' psychographics and emotional needs to 'design emotion'. The new role of the fashion designer ‐ the 'Designer-As-Social-Scientist' ‐ takes a much broader view of the consumers' needs. The evolution of the 'place' of the design process will result in products having greater meaning and emotional value; designers standing out in the oversaturated market; and businesses increasing consumer loyalty and resultant sales by offering only those products that are truly desired by their target audience.